Antihyperuricemia Activity Of Kupa (Syzygium polycephalum) Seed Extracts In Male White Mice - Ira Rahmiyani; Trian Nur'aripin; Anisa Pebiansyah; Resha R. Shaleha (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Hyperuricemia is a clinical condition of increasing uric acid in the blood beyond normal. Increasedlevels of uric acid can accumulate monosodium urate crystals. Kupa fruit seeds contain flavonoids,saponins, tannins, and polyphenols which have antihyperuricemia activity. This study aims todetermine the best antihyperuricemia activity of several kupa seed extracts. The study was conductedin vivo using male white mice. Negative, positive, n-hexane extract, ethanol extract, and ethyl acetateextract were induced by acetylsalicylic acid 5.04 mg/20gBW of mice and fructose 67.2 mg/20gBWof mice orally for 3 days. On the 3rd day of treatment, the positive group was given allopurinol 0.997mg/20gBW and the 3 test groups were each given a different extract of 1.82 mg/20gBW mice orallyfor 7 days. The results showed the ethanol extract of Kupa fruit seeds had the best antihyperuricemiaactivity with a decrease in uric acid levels of 68.29%. Based on the results, the group of mice treatedwith ethanol extract had significantly different activity from the negative control group p <α (0.015<0.05). The ethanol extract showed the best antihyperuricemia activity approaching allopurinol as apositive control.